The Link between Leisure Involvement and Service Performance: Evidence from Frontline Staff Employees in Culinary Industries - Olivia Sri Kartika (Prosiding Industrial Research Workshop and National Seminar, 2018)
Many studies have examined the service frontline staff performance of various industries but rarely found to be associated with leisure involvement in the culinary industry. This study discusses how the relationship between leisure involvement to service performance with variable subjective well-being as intervening. To test this research model is used PLS or partial least squares modelling, by taking a sample from frontline staffs culinary place which amounts to 313 samples in Bandung City, Indonesia. The results of this study found that there is a significant relationship between leisure involvement in service performance and subjective well-being. In conclusion, an employee who is often involved in leisure activities is likely to be happy and will result in their performance in serving customers to be good, this is also influenced by their satisfaction with their work, although the results are not too significant. The implication in managerial that the businessmen need to pay attention to the welfare of employees to service performance given high value.